The Implications of Vitamin D Status During Pregnancy on Mother and her Developing Child - Wagner, Carol L.; Hollis, Bruce W. (Frontiers in Endocrinology, 2018)
Pregnancy is a time of tremendous growth and physiological changes for mother and her developing fetus with lifelong implications for the child. The concert of actions that must occur so mother does not reject the foreign tissue of the fetus, whose source is also paternal is substantial. There must be exquisite balance between maternal tolerance to these foreign proteins of paternal origin but also immune surveillance and function such that the mother is not immunocompromised. When this process goes awry, the mother may experience such pregnancy complications as preeclampsia and infections. Vitamin D deficiency has been implicated in these processes. Controversy continues with regard to the optimal daily intake of vitamin D, when sunlight exposure should be taken into account, and how to define sufficiency during such vulnerable and critical periods of development. The importance of vitamin D supplementation during pregnancy in preventing some of the health risks to the mother and fetus appears linked to achieving 25(OH)D concentration of at least 40 ng/mL, the point at which conversion of vitamin D metabolite 25(OH)D, the prehormone, to 1,25(OH)2D, the active hormone, is optimized. Significant amounts of vitamin D–whether their source is sunlight or supplement–are required during pregnancy to protect mother and fetus and impart genomic imprinting on the fetus to ensure long term health. There is a growing need for future research endeavors to focus not only on critical period(s) leading up to conception and during pregnancy, but throughout life to prevent epigenetic changes that affect health. There is urgency based on emerging research to correct deficiency and maintain optimal vitamin D status. The impact of vitamin D and its metabolites on genetic signaling during pregnancy in both mother and her developing fetus is an area of great activity and still in its early stages. While vitamin D repletion during pregnancy minimizes the risk of certain adverse outcomes (e.g., preterm birth, asthma, preeclampsia, and gestational diabetes), the mechanisms of how these processes occur are not fully understood. As we intensify our research efforts in these areas, it is only a matter of time that such mechanisms will be defined.